Analysis of Productive Waqf Implementation in Community Economic Empowerment at Baitul Muttaqin Mosque, Brebes, Central Java - Adhim, Muhammad Farid Abdullah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Implementation of productive waqf at Baitul Muttaqin Mosque, Brebes Regency, Central Java in the management of waqf assets, such as land and buildings, which are converted into productive businesses that can generate income. The income generated from this business is used to fund various community empowerment programs. This study aims to analyze the implementation of productive waqf at Baitul Muttaqin Mosque, Brebes Regency, Central Java, and to identify obstacles and solutions in empowering the community economy. Management of productive waqf at Baitul Muttaqin Mosque, Brebes Regency, Central Java is also supported by training and education for administrators and congregations, ensuring that management runs effectively. This study is an empirical legal study with a qualitative approach that aims to analyze the implementation of productive waqf in empowering the community's economy at the Baitul Muttaqin Mosque, Brebes, Central Java. A qualitative approach is used to gain an in-depth understanding of the concept of productive waqf applied in the local context, as well as its impact on the economic welfare of the local community. The data analysis method used is descriptive, where the researcher describes the process of managing waqf assets and the forms of businesses developed, as well as their impact on the economic life of the community. In addition, this study uses two theories as analytical tools in data processing, namely the theory of the workings of law and the theory of legal effectiveness. The main focus of this study is to understand how productive waqf is managed by mosque administrators and community participation in the process. The results of this productive waqf show great potential in empowering the community and supporting sustainable social development.